High Performance Interval Training - Wright, G. (2001)
If it were possible to patent a training method then I would register the process and system I have described here. You can't do this so with Stuart's approval we are happy to share it with the world at large and Stuart is the proof of the benefits that can accrue. The benefits in Stuart's case also come from the effort he is prepared to put into his interval sessions. His motivation to train hard is very high and he will push himself to extreme efforts: far harder than your average club time-triallist. In the six week period leading up to the 2001 National 25-mile Time Trial Championship he undertook some 15 structured sessions of pyramid intervals in various combinations [numbers of intervals in each phase etc.] depending on the day of the week and where he was in his training cycle. He is now a strong and very durable athlete and he is able to absorb a high volume of this intense work. If you choose to use this approach don't expect to become a competition record breaker, but with careful planning and control and very good recovery days you might see some dramatic results for already very fit riders who are very committed and motivated. But be careful: the risk of serious short-term overtraining is high with this method. As a final thought I can say the experience of working with Stuart Dangerfield has taught me what many of us have suspected back down through the years: if you want first class athletic results you have to train extraordinarily hard. The trick is to do it smartly.